A Unique ‘Chain Tree’ Bauhinia (Caesalpinioideae, Leguminosae) from Pagerwunung Darupono Conservation Park, Central Java, Indonesia - Lianah, Lianah (Department of Agronomy and Horticulture, IPB University, 2016)
A tree species having a unique stem morphology has been found to grow at Sam Poo Kong temple, Gunung Batu, Semarang city, and at Pager Wunung Darupono Conservation Park, Central Java, about 30 km away from the temple. Based on plant key reference identification the name of this tree species is Bauhinia scandens Willd, a liana from Leguminosae family. This species has a local name of ‘pohon rantai’ due to the chain shape of the stems. It flowered in August and the fruits matured in October. In vitro germination of the seeds collected from the Conservation Park was not successful and only one out of 30 seeds germinated in vivo after 12 weeks. Further studies should be conducted on conservation and propagation of this unique species.